The effect of hypnotherapy on the quality of life in women with breast cancer - Téllez López, Arnoldo; Juárez García, Dehisy Marisol; Jaime Bernal, Leticia; Medina de la Garza, Carlos Eduardo; Sánchez, Teresa J. (2017)
Background. Cancer is a chronic disease that significantly affects the quality of life of patients who suffer from it, because they must face stressful situations, including their diagnosis, surgical procedures, and the adverse effects of chemotherapy and radiotherapy. Objective. To evaluate the effects of hypnotherapy on breast cancer patients’ quality of life during chemotherapy. Design. A quasi-experimental design was used with a convenience sample. Method. Two groups of patients with early breast cancer diagnoses were assigned to either a control group that received standard medical care (n = 20), or a hypnotherapy group (n = 20) that received 12 intensive sessions over the course of 1 month, and 12 additional sessions over the course of 6 months. The patients’ quality of life was evaluated using the European Organization for the Research and Treatment of Cancer Quality of Life Questionnaire Core 30 (EORTC QLQ-C30). Results. The hypnotherapy group showed a statistically significant improvement and a large effect size on the cognitive functioning and social functioning scales compared to the control group. The physical functioning, role functioning, and quality of life scales showed improvement with a medium effect size, but the changes were not statistically significant. Conclusion. The improvement observed in the cognitive functioning and social functioning scales allows us to suggest that hypnotherapy improves the quality of life of breast cancer patients during chemotherapy. Keywords: hypnotherapy, quality of life, breast cancer, cognitive functioning and social functioning